Transport properties / behaviour of Carburization using Molten Salt Technique for Metallurgical applications - Yeo K. B @ A. N.; Mohamed Harimi; Dg. Nooremah Ag. Said; Liau, Chung Fan (Universiti Malaysia Sabah, 2006)
Molten salt electrolytic carburisation process using carbonate salt has been identified as a method to eliminate the toxic cyanide bath in the conventional method of molten salt carburisation. A preliminary research work was to identify methods of molten salt carburization and suitable sample analysis to determine the effectiveness of carburisation process. Modification and design of electro-carburisation process was successfully developed in this research work. The electro-carburisation was carried out in-lab close system with introduction of CO2 and inert Sn02 as anode and mild steel as cathode. The initial usage of graphite anode had shown pitting after the electrolysis and severe corrosion with long term electrolysis. Therefore, graphite anode was replaced with tin oxide anode for the electrolysis system. Two types of salts mixture were use in this research such as 0.8 Na2CO3-0.2 NaCl and 0.5 L12CO3-0.5 K2C03 molar ratio. Cell voltages applied to the electrolytic process, carbon dioxide gas flow rate, the period of carburisation, and the type of carbonate salt has been identified as parameters that affects the carburisation process. Studies on the potential applied on samples electro-carburised in Na2CO3-NaCI and Li2CO3-K2CO3 salts has been carried out and has shown that a minimum of 2.5 V cell voltages for Na2CO3-NaCI salts mixture and a minimum of 2.0 V cell voltages for Li2CO3-K2CO3 are necessary to achieve a maximum carburisation of mild steel in 60 min. Carburisation in Li2CO3-KZCO3 salts is also found to be more effective that required lower energy or molten temperature as compared to electro-carburisation in Na2CO3-NaCI salts. Quenching after electro-carburisation process is found necessary to ensure effective carburising. Non-quenched samples have also shown to characterise a softer and ductile properties although electro-carburised at higher cell voltages. Comparing the electro-carburisation process with the molten cyanide process and other molten salt carburisation, the electro-carburisation process has shown to be more efficient than the conventional toxic cyanide bath (8-11% NaCN) carburisation, and other non-cyanide molten salt carburisation. The case depth of mild steel sample electro-carburised has achieved 0.62 mm. I ligher carburising temperature (above 920 °C) was required for other method to achieve such comparable case depth. Ongoing testing/analysis for microstructure and Vickers hardness analysis such as the effects of C02-N2 gas mixture, the carburising period and variation of Na2CO3-NaCI molar ratio is continuously pursued. Future work shall hope to focus on the usage of various carbonate salts mixture, i. e. Li2CO3-Na2CO3 and Na2CO3-K2CO3.